The Role of Gamification in Enhancing Learning through Neuropsychological Tools: A Narrative Analysis - Antonopoulou, Hera (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper addresses the use of gamification in educational settings with the help of neuropsychological tools. It traces the theoretical foundations of neuropsychology and gamification, and which cognitive processes are affected by these methods to improve learning. This article is going to present design principles on how to combine gamification with neuropsychological tools and analyze their efficacy in education. It also identifies the ethical considerations that are central to the implementation of these tools. It further discusses advanced technologies, including artificial intelligence and virtual reality, for their potential in personalized neuropsychological rehabilitation and educational interventions. This paper emphasizes the importance of interdisciplinary collaboration in overcoming challenges and developing innovative solutions in this field by providing a comprehensive review of current research spanning education, neuroscience, and technology.